Multi-scale and spatially resolved hydrogen mapping in a Ni–Nb model alloy reveals the role of the δ phase in hydrogen embrittlement of alloy 718. (1st May 2016) - Tarzimoghadam, Z.; Rohwerder, M.; Merzlikin, S.V.; Bashir, A.; Yedra, L.; Eswara, S.; Ponge, D.; Raabe, D.
Abstract: We investigated the hydrogen distribution and desorption behavior in an electrochemically hydrogen-charged binary Ni–Nb model alloy to study the role of δ phase in hydrogen embrittlement of alloy 718. We focus on two aspects, namely, (1) mapping the hydrogen distribution with spatial resolution enabling the observation of the relations between desorption profiles and desorption sites; and (2) correlating these observations with mechanical testing results to reveal the degradation mechanisms. The trapping states of hydrogen in the alloy were globally analyzed by Thermal Desorption Spectroscopy (TDS). Additionally, spatially resolved hydrogen mapping was conducted using silver decoration, Scanning Kelvin Probe Force Microscopy (SKPFM) and Secondary Ion Mass Spectrometry (SIMS): The Ag decoration method revealed rapid effusion of hydrogen at room temperature from the γ-matrix. The corresponding kinetics was resolved in both, space and time by the SKPFM measurements. At room temperature the hydrogen release from the γ-matrix steadily decreased until about 100 h and then was taken over by the δ phase from which the hydrogen was released much slower. For avoiding misinterpretation of hydrogen signals stemming from environmental effects we also charged specimens with deuterium. The deuterium distribution in the microstructure was studied by SIMS. The combined results reveal that hydrogen dissolves more preferably inside the γ-matrix and is diffusible at room temperature while the δ phase acts as a deeper trapping site for hydrogen. With this joint and spatially resolving approach we observed the microstructure- and time-dependent distribution and release rate of hydrogen with high spatial and temporal resolution. Correlating the obtained results with mechanical testing of the hydrogen-charged samples shows that hydrogen enhanced decohesion (HEDE) occurring at the δ/matrix interfaces promotes the embrittlement. Graphical abstract: